Palbociclib and Michael-acceptor hybrid compounds as CDK4/6 covalent inhibitors: Improved potency, broad anticancer spectrum and overcoming drug resistance. (15th April 2023) - Fang, Lei; Chu, Mengqi; Yan, Changhang; Liu, Yilin; Zhao, Zimeng
Graphical abstract: Abstract: To search for potent CDK4/6 covalent inhibitors, total 14 compounds have been designed and synthesized by connecting different Michael-acceptor to the piperazine moiety of palbociclib. All the compounds displayed good antiproliferative activity against human hepatoma cell (HepG2), non-small cell lung cancer (A549), and breast cancer (MDA-MB-231 and MCF-7) cell lines. In particular, compound A4 showed the highest inhibitory activity to MDA-MB-231 and MCF-7 cells with IC50 values of 0.51 μM and 0.48 μM, respectively. More importantly, A4 also showed strong inhibition against MDA-MB-231/palbociclib cells, indicating that A4 could effectively avoid the resistance of palbociclib. In the enzyme test, A4 showed selective inhibitory activity against CDK4/6, with the IC50 value of 18 nM and 13 nM, respectively. It was also found that A4 could efficiently induce apoptosis and arrest the cell cycle at G0/G1 phase. Moreover, A4 could significantly decrease the phosphorylation level of CDK4 and CDK6. HPLC and molecular modeling studies suggested that A4 could form a covalent bond with the target protein.